Design of Cottage and Recreation Area in Sibolga City with a Tropical Architectural Approach - Yoan Desyoni Nainggolan; Beny OY Marpaung (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Sibolga City, located along the seashore and endowed with abundant natural beauty, holds significant potential for development as a marine tourism destination. Beyond its coastal appeal, the city offers opportunities for diverse recreational areas such as camping grounds, botanical gardens, culinary centers, and Mancakrida zones. To support these initiatives, this research investigates the sources of activities and spatial programs that can be realized through the construction of cottages and integrated recreational facilities. Given Sibolga’s hot tropical climate, the application of Tropical Architecture is essential to address environmental challenges including solar exposure, rainfall intensity, air humidity, and wind orientation. This study aims to harness Sibolga’s environmental assets by proposing sustainable cottage designs and recreational spaces that align with the principles of Tropical Architecture. The research contributes to the development of commercial residential models that are harmoniously integrated with nature, promoting economic sustainability and ecological balance. Methodologically, the study involves interviews, site surveys, and comparative analyses to derive contextual design solutions. The final output is a conceptual design for cottages and recreational areas that reflect climate-responsive architecture and support Sibolga’s tourism growth. This research not only enhances architectural knowledge in tropical settings but also offers practical insights for urban planners and stakeholders seeking to revitalize Sibolga City as a vibrant, nature-integrated tourism hub.